2006
DOI: 10.1038/sj.onc.1209719
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL promotes metastasis of human pancreatic ductal adenocarcinoma

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has attracted considerable attention for its potential use in tumor therapy, as some recombinant variants of this ligand induce apoptosis in tumor cells without harming most normal cells. Here, we show that TRAIL strongly induces the expression of the proinflammatory cytokines interleukin-8 and monocyte chemoattractant protein 1 and enhances the invasion of apoptosis-resistant pancreatic ductal adenocarcinoma cells in vitro by upregulation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
169
3
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(182 citation statements)
references
References 25 publications
9
169
3
1
Order By: Relevance
“…Several lines of evidence indicate that TRAIL treatment of normal human endothelial cells and apoptosis resistant tumor cell lines can stimulates production of proinflammatory cytokines and chemokines, e.g. IL-1, IL-8, and MCP-1 [14][15][16][17]. We found that TRAIL stimulates production of IL-8 in all three tested human tumor cell lines, RANTES in MCF-7 cells, and bFGF in H460 cells.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Several lines of evidence indicate that TRAIL treatment of normal human endothelial cells and apoptosis resistant tumor cell lines can stimulates production of proinflammatory cytokines and chemokines, e.g. IL-1, IL-8, and MCP-1 [14][15][16][17]. We found that TRAIL stimulates production of IL-8 in all three tested human tumor cell lines, RANTES in MCF-7 cells, and bFGF in H460 cells.…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, TRAIL treatment stimulated proliferation of apoptosis-resistant malignant cells, such as leukemia, neuroblastoma, renal cell carcinoma, and colon carcinoma cell lines [8,12,13]. Moreover, TRAIL promoted metastasis of pancreatic tumors in vivo [14]. In addition, TRAIL can stimulate proinflammatory signaling, leading to increased production of IL-8, IL-1α, IL-1β, and MCP-1 cytokines in normal human endothelial cells and in several apoptosis resistant tumor cell lines [14][15][16][17].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, proliferative effects in response to TRAIL have been reported in vitro using glioma and small cell lung cancer cell lines (Belyanskaya et al, 2008;Vilimanovich and Bumbasirevic, 2008) (Figure 2c). In other case, mice in which Bcl-xl-overexpressing Colo357 pancreatic ductal carcinomas were orthotopic transplanted formed more metastases upon TRAIL treatment (Trauzold et al, 2006), and finally two studies with blasts from leukemia patients treated ex vivo report effects of TRAIL exposure ranging from triggering of cell death to induction of cell proliferation (Ehrhardt et al, 2003;Hasegawa et al, 2005). TRAIL-induced proliferative effect has also been reported in synoviocytes from human rheumatoid patients who exhibit a poorly understood biphasic response to the cytokine, as it triggers death in an initial phase but support proliferation for the persisting/resistant cell fraction (Morel et al, 2005).…”
Section: Novel Paradigms For Cancer Therapy V Pavet Et Almentioning
confidence: 99%